1999
DOI: 10.1093/geronb/54b.6.p347
|View full text |Cite
|
Sign up to set email alerts
|

Some Limits on Encoding Visible Speech and Gestures Using a Dichotic Shadowing Task

Abstract: Visible speech and gestures are two forms of available language information that can be used by listeners to help them understand the speaker's meaning. Previous research has shown that older adults are particularly dependent on visible speech, yet seem to profit less than younger adults from the speaker's gestures. To understand how visible speech and gestures are used when listening becomes difficult, the authors conducted an experiment with a dichotic shadowing task. The experiment examined how accurately p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…In Thompson (1995), while the older adults relied more on visible speech than younger participants, gesture was shown to help younger adults recall sentences but was of little help to older adults. Thompson and Guzman (1999) also found that while young adults benefited from gesture and visible speech in difficult listening conditions, the older adults did not. They suggested that the difference in the impact of gesture on recall may be related to the cognitive changes associated with aging, particularly due to reduced working memory capacity.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In Thompson (1995), while the older adults relied more on visible speech than younger participants, gesture was shown to help younger adults recall sentences but was of little help to older adults. Thompson and Guzman (1999) also found that while young adults benefited from gesture and visible speech in difficult listening conditions, the older adults did not. They suggested that the difference in the impact of gesture on recall may be related to the cognitive changes associated with aging, particularly due to reduced working memory capacity.…”
mentioning
confidence: 86%
“…The only study on gesture imitation also suggests that older adults are less accurate and slower at imitating gesture (Dimeck, Roy, & Hall, 1998). Finally, researchers have found that older adults are worse at naming and categorising pantomime gestures (Ska & Croisile, 1998), at identifying emotional gestures (Montepare, Koff, Zaitchik, & Albert, 1999) and at using gesture as a strategy to support verbal language (Thompson, 1995;Thompson & Guzman, 1999). These studies make an important contribution to our understanding of how aging impacts on gesture comprehension but there are some unanswered questions that remain.…”
mentioning
confidence: 99%
See 3 more Smart Citations